The synergistic effect of nickel-iron-foam and tripolyphosphate for enhancing the electro-Fenton process at circum-neutral pH. (June 2018) - Deng, Fengxia; Olvera-Vargas, Hugo; Garcia-Rodriguez, Orlando; Qiu, Shan; Yang, Jixian; Lefebvre, Olivier
Abstract: A composite nickel-iron-foam (Ni-Fe-F) electrode was used as a cathode in the electro-Fenton (EF) process at circum-neutral pH in the presence of sodium tripolyphosphate (TPP) as supporting electrolyte. It was found that phenol degradation was dramatically improved by the synergistic effect of Ni-Fe-F and TPP, reaching 100% removal in 40 min, with k app = (8.90 ± 0.12) × 10 −2 min −1, which was about 18 times higher than that of Ni-Fe-F with sulfate as conventional electrolyte at pH 3.00 ( k app = (5.00 ± 0.14) × 10 −3 min −1 ). A (75.00 ± 1.67)% mineralization yield was attained after 4-h treatment time. Ni-Fe-F proved capable of providing the Fe 2+ ions necessary to catalyze the Fenton's reaction via a controlled chemical/electrochemical redox process. In addition, Ni-Fe-F promoted the chemical and electrochemical generation of H2 O2 . With respect to TPP, its chelation with Fe ions prevented iron precipitation at neutral and higher pH values, extending the pH range of the Fenton's reaction. Furthermore, the TPP ligand promoted the activation of molecular O2 for the chemical production of OH, enhancing the process efficiency. By overcoming these common limitations of conventional EF in K2 SO4 electrolyte, the Ni-Fe-F/TPP system represents a more sustainable alternative for practical application of EF. A degradation pathway for phenol mineralization with homogeneous and heterogeneous OH produced by the EF Ni-Fe-F/TPP system is proposed based on the identification of the oxidation by-products. Graphical abstract: Image 1 Highlights: The synergic effects of TPP and Ni-Fe-F enhanced the efficiency of the EF process at near neutral pH. The Ni-Fe-F cathode provided the Fe 2+ ions necessary for the Fenton's reaction. TPP served as both chelating agent and OH generator through the Fe(II)-TPP complex. Homogeneous OH were the main oxidant species formed during the degradation process. Both homogeneous and heterogeneous Fenton reactions contributed to phenol degradation and mineralization.